EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION BERBANTUAN MEDIA DUIT TERHADAP PENINGKATAN KETERAMPILAN KOLABORASI PESERTA DIDIK - Mariny Soraya Raupu (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
One of the purposes of the learning activity on Curriculum 2013 is improving collaboration skills. However, the students' collaborative skill at the seventh graders of SMP PGRI Otam is poor, due to the minimum availability of learning facilities, infrastructure, and media. This study investigates the effectiveness of the Group Investigation (GI) learning model assisted with the Investigation, Recycling, Information and Technology acronym DUIT for improving the student's collaborative skills at the seventh graders of SMP PGRI Otam. DUIT starts in designing media from recycled materials and collaborating with information technology products in the learning process. In this research, the solar system media is uploaded through the learning house portal, YouTube, and other learning resources. This research employed a quasi-experimental design with “Two-group posttest only”, where the teacher compared the final collaboration skills from the class given DUIT media-assisted GI learning model with a control class. To obtain the data, this research using observation sheets. The results showed that there were significant differences between the experimental group and the control group. Finally, it can be concluded that the DUIT media-assisted GI learning model enhances the effectiveness and collaboration skills of the seventh-grade students of SMP PGRI Otam.